Pemahaman Andragogi dan Pedagogi dalam Pelatihan: Suatu Tinjauan Filosofis - Andra Eka Putra (Jurnal Kewidyaiswaraan, 2019)
The learning approach that used in basic training for civil servants, leadership training, technical training and functional training are adult learning approach or andragogy that popularized by Malcom Knowles (1913-1977) which are generally positioned as vis a vis with pedagogical learning approaches. This positioning occurs because the position is only viewed from its etymological meaning. This study then intends to review the position of its philosophical aspects where the result of the study show that the origin of andragogy is not vis a vis opposite with pedagogy as long as the pedagogy refers to the critical pedagogy that popularized by Paolo Freire (1921-1997). In fact, some philosophical identities are found between andragogy and critical pedagogy.